Impact of smart device use on objective and subjective health of older adults: findings from four provinces in China - Wei, Yan; Guo, Xinyu (Frontiers in Public Health, 2023)
Background: The digital divide has grown because of the deepening digitalization of the Chinese society and the intersection between high-end technology and the age structure. Older adults show an increasing level of weakness in digital life integration. What digital development can bring to older adults is a pressing concern. Objective: This study aims to investigate how smart device use affects older adults’ health status and offers an empirical reference for improving their digital literacy and health. Methods: The data in this study were collected from an offline survey conducted from December 2021 to April 2022, which obtained 1110 valid samples of older adults This study used a multivariate ordered logit model, mediating effect model, and heterogeneity test to analyze the impact of smart device use on the health status of older adults. Results: Smart device use has a significant positive effect on the self-rated, physical, and psychological health of older adults, and this positive effect is more pronounced among older adults living in urban areas or with a higher age. The average net effect of smart devices on each health status of older adults is 0.161 for self-rated health, 0.155 for physical health, and 0.071 for psychological health. In-depth research found that older adults’ attitudes towards smart devices played a mediating role in the influence of smart device use on self-rated and psychological health respectively. Conclusions: The study found that smart device use had a positive effect on the health status of older adults and that the performance expectations and individualized needs of older adults exhibited an effective linkage between smart devices and health status. Smart device use could improve the overall health of older adults, especially the urban and low-age older adults. Promoting the understanding of the practicality of smart devices for older adults and the aging-oriented transformation of smart devices is an effective way to improve the health status of older adults. The findings provide theoretical support for the wide application of smart devices in older adults and can effectively help eHealth practitioners implement accurate geriatric health support strategies.